The Waste-Resource Paradox: Practical dilemmas and societal implications in the transition to a circular economy. (20th June 2021) - Greer, Rachel; von Wirth, Timo; Loorbach, Derk
Abstract: The European Union has vowed to transition from a linear to a circular economy (CE). Many innovations, new business models, and policies have begun to emerge to support the push for further institutionalizing CE practices. A large portion of these attempts are based on transforming a flow currently labeled as a waste stream into a value proposition, i.e. a resource. However, this ironically increases the risk of creating a demand for these waste streams, which thereby may become commodified. In this article, we unpack the inherent dilemmas and implications created by this phenomenon, which we define as the Waste-Resource Paradox (WRP). Understanding the WRP is highly relevant, as its manifestation may lead to situations in which the further establishment of "circular" practices may reinforce linear economy by sustaining a waste (over)production in the system or causing undesired social or environmental repercussions. This can tighten a lock-in of the existing linear structures counteractive to CE that have not been explicitly identified or explored to date. We observed that the WRP may evolve and morph throughout time, across boundaries or respective to different societal sectors. Based on our findings, we highlight the profound implications of the WRP for the future of circularity and the potential consequences for a transition to CE. Graphical abstract: Image 1 Highlights: Transitioning to a circular economy (CE), the Waste-Resource Paradox (WRP) emerges. Some "circular" innovations may actually increase linear economy path dependencies. The WRP exposes four key practical dilemmas and the resulting implications for CE. Policymakers, investors, and entrepreneurs must consider the WRP in decisions.